Brief analysis of the desaposentação institute: right acquired or aggravating factor of system crisis brazilian social securuty? - Soares, Fernanda Heloisa Macedo (2016)
The desaposentação institute has been the subject of great controversy in the Social Security Law, because despite not being provided by the Brazilian Legal System, and therefore can not be accepted administratively, but the judiciary its implications. Thus, this study aims to analyze if the desaposentção is acquired right of the worker after his retirement continues to contribute an so you want to have your updated benefit or to accept such a possibility will become an aggravating factor of the Brazilian Social Security system crisis.